A composite rubber material and preparation method thereof

By using sodium hexametaphosphate and benzimidazole modified calcined kaolin as filler, combined with a blend of styrene butadiene rubber and butadiene rubber, a composite rubber material with high wear resistance and high strength was prepared, and the existing rubber material was solved. Problems of wear resistance and insufficient strength, suitable for sports floors and rubber rolls.

CN118404871BActive Publication Date: 2024-12-13HEBEI ENLIO SPORTS GOODS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410443714.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-13
Publication Date
2024-12-13
Estimated Expiration
2044-04-13

AI Technical Summary

Technical Problem

The wear resistance and strength of existing rubber materials are insufficient, and the inorganicity and agglomeration of fillers limit the properties of the material.

Method used

Use sodium hexametaphosphate and/or benzimidazole modified calcined kaolin as filler to improve the dispersion and compatibility of calcined kaolin through adsorption and reaction, and combine a blend of styrene butadiene rubber and butadiene rubber to prepare a wear-resistant layer and a composite rubber material of foam layer.

Benefits of technology

It significantly improves the wear resistance and strength of rubber materials, provides good anti-slip effect and hardness, has a tensile strength of more than 13.82MPa, and an abrasion volume of less than 0.190cm3. It is suitable for sports floors and rubber rolls.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of rubber technology, and proposes a composite rubber material and a preparation method thereof. A composite rubber material comprises a wear-resistant layer and a foaming layer from top to bottom; the raw materials of the wear-resistant layer comprise the following components by mass: 60 parts of styrene-butadiene rubber, 40 parts of butadiene rubber, 8 to 12 parts of activator, 50 to 60 parts of filler, 4 to 8 parts of softener, 1 to 4 parts of antioxidant, 1 to 3 parts of vulcanizer, and 3 to 5 parts of accelerator; the filler is calcined kaolin modified by a modifier; the modifier comprises sodium hexametaphosphate and / or benzimidazole. Through the above technical scheme, the problems of poor wear resistance and low strength of rubber materials in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of rubber technology, and in particular to a composite rubber material and a preparation method thereof. Background Art

[0002] Rubber materials are polymer materials with good elasticity, viscoelasticity, and electrical insulation. They are widely used in conveyor belts, sports floors, waterproof rolls, etc. According to the characteristics of rubber, it can be divided into cis-butadiene rubber, styrene-butadiene rubber, nitrile rubber, chloroprene rubber, silicone rubber, fluororubber, etc. Among them, styrene-butadiene rubber has good wear resistance, natural aging resistance, ozone resistance, water resistance and heat resistance, but poor elasticity, while cis-butadiene rubber has good elasticity. Therefore, the blend of styrene-butadiene rubber and cis-butadiene rubber not only has the advantages of styrene-butadiene rubber, but also improves the disadvantage of poor elasticity of styrene-butadiene rubber through cis-butadiene rubber, so it has good comprehensive performance and is widely used.

[0003] Fillers need to be added to existing rubber materials to improve the wear resistance and strength of the materials. However, since the fillers themselves are inorganic and easy to agglomerate, the wear resistance and strength of the rubber materials are limited. Summary of the invention

[0004] The invention provides a composite rubber material and a preparation method thereof, which solves the problems of poor wear resistance and low strength of the rubber material in the related art.

[0005] The technical solution of the present invention is as follows:

[0006] A composite rubber material, comprising a wear-resistant layer and a foaming layer from top to bottom; the raw materials of the wear-resistant layer include the following components in parts by mass: 60 parts of styrene-butadiene rubber, 40 parts of butadiene rubber, 8-12 parts of activator, 50-60 parts of filler, 4-8 parts of softener, 1-4 parts of antioxidant, 1-3 parts of vulcanizer, and 3-5 parts of accelerator;

[0007] The filler is calcined kaolin modified by a modifier; the modifier includes sodium hexametaphosphate and / or benzimidazole.

[0008] As a further technical solution, the foaming layer is a natural rubber foaming material.

[0009] As a further technical solution, the mass ratio of the modifier to the calcined kaolin is 3~8:60.

[0010] As a further technical solution, when the modifier includes sodium hexametaphosphate and benzimidazole, the mass of sodium hexametaphosphate is higher than that of benzimidazole.

[0011] The present invention limits the modifier to sodium hexametaphosphate and benzimidazole, and limits the mass of sodium hexametaphosphate to be higher than that of benzimidazole, thereby further improving the wear resistance and strength of the rubber material. The reason is that: firstly, sodium hexametaphosphate will be adsorbed on the surface of calcined kaolin, giving the surface of calcined kaolin phosphorus-oxygen double bonds, and at the same time, benzimidazole can react with the surface of calcined kaolin phosphorus-oxygen double bonds, and be grafted on the surface of calcined kaolin, which not only improves the dispersibility of calcined kaolin, but also improves the compatibility of calcined kaolin with the rubber matrix.

[0012] As a further technical solution, the mass of the sodium hexametaphosphate is 1.5 times higher than that of benzimidazole.

[0013] As a further technical solution, the mass ratio of the sodium hexametaphosphate to benzimidazole is 4:1 to 3.5:1.5.

[0014] The present invention limits the mass ratio of sodium hexametaphosphate to benzimidazole to 4:1-3.5:1.5, thereby further improving the wear resistance and strength of the rubber material.

[0015] As a further technical solution, when the modifier includes sodium hexametaphosphate or benzimidazole, the preparation method of the filler includes the following steps: uniformly mixing calcined kaolin, the modifier and the solvent, filtering and drying to obtain the filler;

[0016] When the modifier includes sodium hexametaphosphate and benzimidazole, the preparation method of the filler includes the following steps: after calcined kaolin, the modifier and the solvent are uniformly mixed, pyridine is added to react, filtered and dried to obtain the filler.

[0017] As a further technical solution, the reaction includes a first stage reaction and a second stage reaction, the first stage reaction temperature is 3-5°C and the time is 1-3h, and the second stage reaction temperature is 20-30°C and the time is 7-10h.

[0018] As a further technical solution, the activator includes zinc oxide and / or stearic acid;

[0019] Softeners include aromatic oils and / or pine tar;

[0020] The antioxidant includes antioxidant BLE and / or antioxidant 4010NA;

[0021] The vulcanizing agent includes sulfur and / or peroxide;

[0022] The accelerator includes accelerator ZDC and / or accelerator H.

[0023] The present invention also proposes a method for preparing a composite rubber material, comprising the following steps:

[0024] S1, after plasticating styrene-butadiene rubber and cis-1,1-butadiene rubber, adding activator, filler, softener, antioxidant for mixing, then adding vulcanizing agent and accelerator for further mixing, calendering into sheets, and obtaining a wear-resistant layer;

[0025] S2, compounding the wear-resistant layer and the foaming layer, and then vulcanizing them to obtain a composite rubber material.

[0026] As a further technical solution, the vulcanization temperature is 150-170° C. and the time is 10-30 minutes.

[0027] The working principle and beneficial effects of the present invention are:

[0028] 1. The present invention uses sodium hexametaphosphate and / or benzimidazole modified calcined kaolin as filler. After sodium hexametaphosphate is used to modify the calcined kaolin, the surface of the calcined kaolin will adsorb the long chains with negative charge formed by sodium hexametaphosphate, thereby improving the dispersibility of the calcined kaolin; and after benzimidazole is used to modify the calcined kaolin, the inorganic property of the surface of the calcined kaolin can be improved, thereby improving the compatibility of the calcined kaolin with the rubber matrix, thereby giving the wear-resistant layer good wear resistance and high strength, and providing a rubber material with good wear resistance and high strength. In addition, the rubber material provided by the present invention also has a good anti-slip effect and a hardness of more than 90 Shao A.

[0029] 2. The present invention adopts a composite rubber material provided by a wear-resistant layer and a foaming layer, wherein the foaming layer has a buffering effect and can return 70-80% of the energy, and can be applied to sports floors and rubber coils. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The parameters of the raw materials in the following examples and comparative examples are as follows:

[0032] The styrene butadiene rubber is styrene butadiene rubber SBR1502;

[0033] Butadiene rubber is butadiene rubber BR9000;

[0034] Calcined kaolin is obtained by calcining coal-based kaolin at 1000°C for 1 h, with a particle size of 2 μm;

[0035] Aromatic content in aromatic oil>84wt%, kinematic viscosity (100℃)8~40m 2 / s;

[0036] The effective substance content in pine tar is 90wt%, pH=4~5;

[0037] The particle size of white clay is 325 mesh;

[0038] The preparation method of the foaming layer is as follows:

[0039] 80 parts of natural rubber SVR CV60 and 20 parts of LDPE 2420H were stirred at 80°C and 60 r / min for 15 minutes, 40 parts of white clay, 3 parts of accelerator M, 5 parts of stearic acid, 3 parts of azodicarbonamide, 0.3 parts of dicumyl peroxide and 3.5 parts of sulfur were added and mixed evenly, then thinly passed 4 times on an open mill with a roller distance of 1 mm, and finally rolled into a film with a thickness of 3 mm on an open mill to obtain a foamed layer.

[0040] Example 1

[0041] S1, 60 g of calcined kaolin, 1 g of sodium hexametaphosphate and 3 L of water were mixed and stirred for 1 h, then filtered and dried to obtain a filler;

[0042] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0043] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0044] Example 2

[0045] S1, 60 g of calcined kaolin, 1 g of sodium hexametaphosphate and 3 L of water were mixed and stirred for 2 h, then filtered and dried to obtain a filler;

[0046] S2, 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber were plasticized at 55°C, 8 parts of zinc oxide, 50 parts of filler, 4 parts of pine tar oil and 1 part of antioxidant 4010NA were added, and the mixture was kneaded at 110°C, and 1 part of sulfur and 3 parts of accelerator H were added and kneaded at 90°C, and the mixture was calendered into a sheet to obtain a wear-resistant layer;

[0047] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 150° C. for 30 minutes to obtain a composite rubber material.

[0048] Example 3

[0049] S1, 60 g of calcined kaolin, 1 g of sodium hexametaphosphate and 3 L of water were mixed and stirred for 3 h, then filtered and dried to obtain a filler;

[0050] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55°C, add 8 parts of zinc oxide, 4 parts of stearic acid, 60 parts of filler, 4 parts of pine tar oil, 4 parts of aromatic oil, 1 part of antioxidant 4010NA, 3 parts of antioxidant BLE, mix at 110°C, add 3 parts of dicumyl peroxide, 3 parts of accelerator H, 2 parts of accelerator ZDC, continue mixing at 90°C, and calender into sheets to obtain a wear-resistant layer;

[0051] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 170° C. for 10 min to obtain a composite rubber material.

[0052] Example 4

[0053] S1, 60 g of calcined kaolin, 3 g of sodium hexametaphosphate and 3 L of water were mixed and stirred for 1 h, then filtered and dried to obtain a filler;

[0054] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0055] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0056] Example 5

[0057] S1, 60 g of calcined kaolin, 5 g of sodium hexametaphosphate and 3 L of water were mixed and stirred for 1 h, then filtered and dried to obtain a filler;

[0058] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0059] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0060] Example 6

[0061] S1, 60 g of calcined kaolin, 8 g of sodium hexametaphosphate and 3 L of water were mixed and stirred for 1 h, then filtered and dried to obtain a filler;

[0062] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0063] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0064] Example 7

[0065] S1, 60 g of calcined kaolin, 10 g of sodium hexametaphosphate and 3 L of water were mixed and stirred for 1 h, then filtered and dried to obtain a filler;

[0066] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0067] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0068] Example 8

[0069] S1, calcined kaolin 60g, benzimidazole 5g and water 3L were mixed and stirred for 1h, then filtered and dried to obtain a filler;

[0070] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0071] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0072] Example 9

[0073] S1, 60g of calcined kaolin, 1.5g of sodium hexametaphosphate, 3.5g of benzimidazole and 3L of water were mixed and stirred for 1h, then cooled to 5°C, and 6g of pyridine was added dropwise. After 40min of addition, the reaction was continued for 2h, and the temperature was raised to 25°C for 8h, filtered, washed with water, and dried to obtain a filler;

[0074] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0075] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0076] Example 10

[0077] S1, 60g of calcined kaolin, 2.5g of sodium hexametaphosphate, 2.5g of benzimidazole and 3L of water were mixed and stirred for 1h, then cooled to 5°C, and 6g of pyridine was added dropwise. After 40min of addition, the reaction was continued for 2h, and the temperature was raised to 25°C for reaction for 8h, filtered, washed with water, and dried to obtain a filler;

[0078] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0079] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0080] Embodiment 11

[0081] S1, 60g of calcined kaolin, 3g of sodium hexametaphosphate, 2g of benzimidazole and 3L of water were mixed and stirred for 1h, then cooled to 5°C, and 6g of pyridine was added dropwise. After 40min of addition, the reaction was continued for 2h, and the temperature was raised to 25°C for 8h, filtered, washed with water, and dried to obtain a filler;

[0082] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0083] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0084] Example 12

[0085] S1, 60g of calcined kaolin, 3.5g of sodium hexametaphosphate, 1.5g of benzimidazole and 3L of water were mixed and stirred for 1h, then cooled to 5°C, and 6g of pyridine was added dropwise. After 40min of addition, the reaction was continued for 2h, and the temperature was raised to 25°C for 8h, filtered, washed with water, and dried to obtain a filler;

[0086] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0087] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0088] Embodiment 13

[0089] S1, 60g of calcined kaolin, 4g of sodium hexametaphosphate, 1g of benzimidazole and 3L of water were mixed and stirred for 1h, then cooled to 5°C, and 6g of pyridine was added dropwise. After 40min of addition, the reaction was continued for 2h, and the temperature was raised to 25°C for 8h, filtered, washed with water, and dried to obtain a filler;

[0090] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0091] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0092] Embodiment 14

[0093] S1, 60g of calcined kaolin, 4.5g of sodium hexametaphosphate, 0.5g of benzimidazole and 3L of water were mixed and stirred for 1h, then cooled to 5°C, and 6g of pyridine was added dropwise. After 40min of addition, the reaction was continued for 2h, and the temperature was raised to 25°C for 8h, filtered, washed with water, and dried to obtain a filler;

[0094] S2, after plasticating 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber at 55° C., add 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of filler, 5 parts of aromatic oil, and 2 parts of antioxidant BLE, mix at 110° C., add 2 parts of sulfur and 4 parts of accelerator ZDC, continue mixing at 90° C., and calender into sheets to obtain a wear-resistant layer;

[0095] S3. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0096] Comparative Example 1

[0097] S1. After 60 parts of styrene-butadiene rubber and 40 parts of butadiene rubber are plasticized at 55° C., 5 parts of zinc oxide, 5 parts of stearic acid, 55 parts of calcined kaolin, 5 parts of aromatic oil, and 2 parts of antioxidant BLE are added and mixed at 110° C., 2 parts of sulfur and 4 parts of accelerator ZDC are added and mixed at 90° C., and the mixture is calendered into a sheet to obtain a wear-resistant layer;

[0098] S2. After compounding the wear-resistant layer and the foaming layer, vulcanize at 160° C. for 20 minutes to obtain a composite rubber material.

[0099] The composite rubber materials obtained in Examples 1 to 14 and Comparative Example 1 were tested for tensile strength according to the method in GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" (dumbbell-shaped specimen 1A type, tensile rate 100 mm / min), and the wear resistance was tested according to the method in GB / T 1689-2014 "Determination of wear resistance of vulcanized rubber (using Akron abrasion tester)". The test results are recorded in Table 1.

[0100] Table 1 Tensile strength and wear volume of composite rubber materials

[0101]

[0102] It can be seen from Table 1 that the tensile strength of the composite rubber material provided by the present invention is above 13.82 MPa, and the wear volume is above 0.190 cm 3 The following has good wear resistance and high strength.

[0103] Compared with Comparative Example 1, Examples 1 to 14 use sodium hexametaphosphate and / or benzimidazole-modified calcined kaolin as fillers, while Comparative Example 1 uses calcined kaolin as filler. The tensile strength of the composite rubber materials obtained in Examples 1 to 14 is higher than that in Comparative Example 1, and the wear volume is lower than that in Comparative Example 1, indicating that sodium hexametaphosphate and / or benzimidazole-modified calcined kaolin can improve the wear resistance and strength of the composite rubber material.

[0104] The tensile strength of the composite rubber material obtained in Examples 11 to 14 is higher than that in the other examples, and the wear volume is lower than that in the other examples, indicating that when sodium hexametaphosphate and benzimidazole modify the calcined kaolin, and the mass of sodium hexametaphosphate is higher than that of benzimidazole, the wear resistance and strength of the composite rubber material can be further improved.

[0105] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite rubber material, characterized in that: The material comprises a wear-resistant layer and a foaming layer from top to bottom; the raw materials of the wear-resistant layer comprise the following components by weight: 60 parts of styrene-butadiene rubber, 40 parts of butadiene rubber, 8-12 parts of activator, 50-60 parts of filler, 4-8 parts of softener, 1-4 parts of antioxidant, 1-3 parts of vulcanizer, and 3-5 parts of accelerator; The filler is calcined kaolin modified by a modifier; the modifier includes sodium hexametaphosphate and benzimidazole, and the mass of sodium hexametaphosphate is higher than that of benzimidazole; The preparation method of the filler comprises the following steps: after calcined kaolin, a modifier and a solvent are uniformly mixed, pyridine is added to react, suction filtered, and dried to obtain the filler; The reaction includes a first stage reaction and a second stage reaction, wherein the temperature of the first stage reaction is 3-5° C. and the time is 1-3 hours, and the temperature of the second stage reaction is 20-30° C. and the time is 7-10 hours.

2. A composite rubber material according to claim 1, characterized in that: The mass ratio of the modifier to the calcined kaolin is 3-8:

60.

3. A composite rubber material according to claim 1, characterized in that: The mass of the sodium hexametaphosphate is 1.5 times higher than that of benzimidazole.

4. A composite rubber material according to claim 3, characterized in that: The mass ratio of the sodium hexametaphosphate to benzimidazole is 4:1 to 3.5:1.

5.

5. The composite rubber material according to claim 1, characterized in that: The activator comprises zinc oxide and / or stearic acid; Softeners include aromatic oils and / or pine tar; The antioxidant includes antioxidant BLE and / or antioxidant 4010NA; The vulcanizing agent includes sulfur and / or peroxide; The accelerator includes accelerator ZDC and / or accelerator H.

6. The method for preparing a composite rubber material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, after plasticating styrene-butadiene rubber and cis-1,1-butadiene rubber, adding activator, filler, softener, antioxidant for mixing, then adding vulcanizing agent and accelerator for further mixing, calendering into sheets, and obtaining a wear-resistant layer; S2, compounding the wear-resistant layer and the foaming layer, and then vulcanizing them to obtain a composite rubber material.

7. The method for preparing a composite rubber material according to claim 6, characterized in that: The vulcanization temperature is 150-170° C. and the vulcanization time is 10-30 minutes.